Physical exertion does not lead to a change in the time taken to correctly recognize stereoscopic stimuli in changing horizontal disparity levels - Frisch, Florian; Mehringer, Wolfgang; Ring, Matthias; Eskofier, Björn; Michelson, Georg (Frontiers in Physiology, 2025)
Background and questionIn elite sports, having good stereoscopic vision is important, especially during significant physical exertion. We investigated whether increased physical exertion leads to changes in the time it takes to correctly recognize stereoscopic stimuli in changing horizontal disparity conditions (latency).Study design and research methodsTwenty-one male and female test subjects, aged 39.0 ± 18.7 years, completed four rounds, each consisting of three attempts. One training round took place with no physical exertion. Then, three rounds took place with low (HR = 100 beats per minute on average), medium (HR = 120 beats per minute on average), and high (HR = 155 beats per minute on average) levels of exertion. These levels of exertion were achieved by using an exercise bike and increasing the power in watts accordingly and by using a pulse oximeter to monitor heart rate. During each attempt, the test subjects were tested for five stereoscopic disparities (32, 128, 192, 256, and 320 arcsec), each presented 16 times for a total of 80 stimuli. Changes in reaction time, percentage of correct answers, and the “GAIN” parameter (reaction time increase per stereo disparity decrease) were recorded.ResultsThe percentage of correct answers does not change with increasing physical exertion, and the reaction time for correctly answering does not increase significantly with increased physical exertion. For example, no significant difference was found in the response time at 32 arcsec between low (803.0 m) and high (745.5 m), p = 0.478.ConclusionPhysical exertion up to heart rates >140/min does not impair the recognition of stereoscopic stimuli at different disparities.